Sher shah suri - Nazar, Zaidi (Feroz sons Karachi, 2003)
Sher Shah Suri is a historical fiction that recounts the life of the great Afghan ruler who established the Sur Empire in India. This book offers a detailed and engaging account of Suri's military campaigns, administrative reforms, and his legacy. Readers will be transported to a time of great political upheaval and learn about the strategies and challenges faced by this formidable leader.